Survey study of the Factors Determining Culex pipiens Mosquitoes Residing Strategy in Al-Furat Al-Awsat Technical University Campus - Hamza Ahmed Aziz Al-Aaraji (Indian Journal of Forensic Medicine & Toxicology, 2020)
The present study surveying more than 1909 mosquitoes with their nests arounds all the campus areas andborders through using of both nets and adhesive papers for collection purposes. Data analysis showing asignificant effects by each of agriculture (60%), rubbish and sewage puddles factors (16%)in the spreading,reproduction and distribution of Culex pipiensspp. in the campus region within probability of P<0.05 as andependent significant result.Conclusion of our project predicting that the location of campus building will ruled and controlling thepercentage of bug’s net spreading and reproduction capabilities.